Combined lateral and transcuneiform without medial osteotomy for residual clubfoot for children - Mahadev, A.; Munajat, I.; Mansor, A.; Hui, J.H.P. (Lippincott, Williams & Wilkins, 2009)
Residual deformity in resistant clubfoot is not uncommon. The "bean-shaped foot" exhibits forefoot adduction and midfoot supination and may interfere with function due to poor foot placement. For children less than 5 years of age we describe a corrective procedure combining a closing wedge cuboidal osteotomy and trans-midfoot rotation procedure without a medial opening wedge osteotomy. We retrospectively reviewed twelve patients (14 feet), mean age 4.7 years (range, 4-5 years), who had undergone the procedure to correct forefoot adduction and midfoot supination deformities. We obtained minimal access via a small lateral skin incision. Cuboid lateral wedge osteotomy was followed by transcuneiform osteotomy using a Kirschner wire as a guide under an image intensifier. The minimum followup was 2 years (mean, 2.6 years; range, 2â3.2 years). All patients had qualitative improvement in correction of adduction and supination deformities. Radiographically there was an improvement in adduction deformity, the mean anteroposterior talo-first metatarsal and calcaneo-fifth metatarsal angles improved by 28Â° (from 40Â° to 12Â°) and by 11Â° (from 21Â° to 10Â°). The supination improved by 11Â° (from 19Â° to 8Â°) and the cavus improved by 17Â° (from 30Â° to 13Â°). The short-term outcome was reliable and this combination is useful for children younger than 5 years old where the medial cuneiform ossification center remained poorly defined.